2008
DOI: 10.1001/archpsyc.65.9.1041
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Left and Reduced Right Orbitomedial Prefrontal Fractional Anisotropy in Adults With Bipolar Disorder Revealed by Tract-Based Spatial Statistics

Abstract: Context Diffusion tensor imaging (DTI) studies in adults with bipolar disorder (BD) indicate altered white matter (WM) in the orbitomedial prefrontal cortex (OMPFC), potentially underlying abnormal prefrontal corticolimbic connectivity and mood dysregulation in BD. Objective To use tract-based spatial statistics (TBSS) to examine WM skeleton (ie, the most compact whole-brain WM) in subjects with BD vs healthy control subjects. Design Cross-sectional, case-control, whole-brain DTI using TBSS. Setting Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
243
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(267 citation statements)
references
References 84 publications
18
243
3
3
Order By: Relevance
“…Compared with HC subjects, patients with anxiety disorder had significantly lower FA localized to the right UF white matter near the orbitofrontal cortex (Phan et al, 2009). Likewise, patients with bipolar disorder showed similar abnormalities in the UF (McIntosh et al, 2008;Versace et al, 2008;Versace et al, 2010). Although we did not find abnormalities in the left UF in our depressed subjects, a previous study demonstrated that bipolar patients exhibited divergent FA changes in the left vs the right UF (greater FA in the left UF and lower FA in the right UF) (Versace et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Compared with HC subjects, patients with anxiety disorder had significantly lower FA localized to the right UF white matter near the orbitofrontal cortex (Phan et al, 2009). Likewise, patients with bipolar disorder showed similar abnormalities in the UF (McIntosh et al, 2008;Versace et al, 2008;Versace et al, 2010). Although we did not find abnormalities in the left UF in our depressed subjects, a previous study demonstrated that bipolar patients exhibited divergent FA changes in the left vs the right UF (greater FA in the left UF and lower FA in the right UF) (Versace et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…As previously mentioned in the Introduction section, these regions have been previously investigated and shown to be altered in several imaging studies on mood disorders. For example, decreased radial diffusivity in the orbitomedial prefrontal cortex was reported in bipolar subjects relative to HC (Versace et al, 2008) and decreased FA in the anterior cingulate cortex was reported in subjects with acute coronary syndrome who developed persistent depression (Rapp et al, 2010). However, further studies are needed to directly examine which specific regions contribute to the FA reduction in the right UF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies show the utility of DTI in neuropsychiatric research. In several studies, treatment of neuropsychiatric patients has also been associated with changes in DTI measures (Versace et al, 2008;Yoo et al, 2007). This also shows the promise of DTI for understanding therapeutic effects.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, when examination is confined to a specific sub-network (as detailed in the following section), localized fiber tracts can be selected by the ROIs, such as anterior cingulate cortex [75,76] , prefrontal cortex [77] , and motor areas [78] . We can also leverage fiber clustering methods [79,80] , or mutually combine with fMRI [81,82] to group fiber tracts that predict different connectivity paths.…”
Section: Tractography For Wmm and Network Constructionmentioning
confidence: 99%